2021
DOI: 10.3390/jmse9080850
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sand Trapping Fences on Dune Toe Growth and Its Relation with Potential Aeolian Sediment Transport

Abstract: This study provides insights into dune toe growth around and between individual brushwood lines of sand trapping fences at the dune toe of coastal dunes using digital elevation models obtained from repeated unmanned aerial vehicle surveys. Prevailing boundary conditions, especially sediment supply, as well as the porosity and arrangement of the installed sand trapping fences significantly influence the effectiveness of different configurations of sand trapping fences. The dune toe growth is significant immedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…Overall, the high fence tended to show higher sand-trapping effectiveness than the medium and low fences. However, above a certain fence height, the efficiency to trap sand decreases [22,29]. Figure 6 Similar developments were observed on fences studied by Hotta and Horikawa (1990) [22] and Eichmanns and Schüttrumpf (2021) [29].…”
Section: Fence Heightsupporting
confidence: 69%
See 4 more Smart Citations
“…Overall, the high fence tended to show higher sand-trapping effectiveness than the medium and low fences. However, above a certain fence height, the efficiency to trap sand decreases [22,29]. Figure 6 Similar developments were observed on fences studied by Hotta and Horikawa (1990) [22] and Eichmanns and Schüttrumpf (2021) [29].…”
Section: Fence Heightsupporting
confidence: 69%
“…Moreover, the investigations of Ning et al (2020) [26] showed that sand-trapping is highest at the beginning of the first phase, drops significantly until the end of the first phase, and continues to drop slowly until the end of the second phase. The dune grows only horizontally during the second phase until a streamlined equilibrium is reached [29,60,61]. Overall, the high fence tended to show higher sand-trapping effectiveness than the medium and low fences.…”
Section: Fence Heightmentioning
confidence: 93%
See 3 more Smart Citations